2021
DOI: 10.1136/openhrt-2021-001650
|View full text |Cite
|
Sign up to set email alerts
|

Patient delay and benefit of timely reperfusion in ST-segment elevation myocardial infarction

Abstract: BackgroundIn patients with ST-segment elevation myocardial infarction (STEMI), it is unknown how patient delay modulates the beneficial effects of timely reperfusion.AimsTo assess the prognostic significance of a contact-to-balloon time of less than 90 min on in-hospital mortality in different categories of symptom-onset-to-first-medical-contact (S2C) times.MethodsA total of 20 005 consecutive patients from the Feedback Intervention and Treatment Times in ST-segment Elevation Myocardial Infarction (FITT-STEMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Multivariable logistic regression analysis also showed that STEMI-equivalent ECG was an independent factor of DTB time delayed for more than 90 min, which is known to be associated with an unfavorable outcome in the study population. Our study also corroborated with previous studies in that delayed DTB time was an independent predictor of in-hospital MACE [ 7 , 8 , 10 , 11 , 13 ], indicating that the principle of valuing every minute for AMI patients might also be applied to patients with STEMI-equivalent ECGs, and timely reperfusion would be beneficial for this study population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Multivariable logistic regression analysis also showed that STEMI-equivalent ECG was an independent factor of DTB time delayed for more than 90 min, which is known to be associated with an unfavorable outcome in the study population. Our study also corroborated with previous studies in that delayed DTB time was an independent predictor of in-hospital MACE [ 7 , 8 , 10 , 11 , 13 ], indicating that the principle of valuing every minute for AMI patients might also be applied to patients with STEMI-equivalent ECGs, and timely reperfusion would be beneficial for this study population.…”
Section: Discussionsupporting
confidence: 90%
“…Reducing the ischemic time from symptom onset to coronary reperfusion is crucial, and door-to-balloon (DTB) time, defined as the time duration from patient arrival at the emergency department (ED) to device placement on an infarct coronary artery, is frequently used as an indicator of adequate pPCI performance [ 6 ]. Previous studies have shown that delayed DTB time is associated with an unfavorable outcome in patients with STEMI [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Therefore, clinical guidelines recommend maintaining shorter ischemic time for these patients [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, D2B time only focuses on the final component of the regional systems of care, and more recently, FMC2B time has been considered a more relevant indicator because it includes all factors involved in the healthcare chain for STEMI patients [ 6 ]. Scholz et al [ 7 ] demonstrated that timely revascularisation with an FMC2B time of < 90 min was a crucial component of improving the in-hospital mortality of STEMI patients, but there was no observation of what happened to the patients after they were discharged from the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic heart disease is one of the leading causes of death in human and timely reperfusion is the most effective method for the treatment of acute myocardial infarction [1]. However, studies have found that reperfusion may cause cardiomyocyte injury and this process is often called myocardial ischemia/reperfusion (I/R) injury [2].…”
Section: Introductionmentioning
confidence: 99%